The “excritura” with the body: eroticism as transgression - Concha López, Teresa (Re-presentaciones: Periodismo, comunicación y sociedad, 2020)
The metaphysical tradition is characterize by giving primacy to "the rational" over “the sensible”. The first element is universal and necessary, while the sensible is the contingent and mutable, therefore perishable. In this thought erected from conceptual binomials such as nature-culture, pathos and logos, sensitivity-understanding, body-soul, woman-man, activity reigns over passivity. From these divisions, we intend to relate two of these oppositions: 1. body-soul and 2. woman-man with the act of writing. Is the writing determined by sex? If you write "with the body", is it always from a sexed body? On the other hand, we are interested in rescuing some ideas from Bataille and Jean-Luc Nancy's thought in order to ask about what Richard calls the “feminization of writing” that would be given by a certain force of subjectivation that goes beyond sexual difference. Finally, we propose that the body and the writing would form an inseparable unit, if they are thought in the terms of Bataille (Eroticism) or Jean-Luc Nancy ("excritura")
Keywords: writing; body; eroticism; soul-body; sexed body